(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
The article describes music circles, their goals and objectives. This information can be used as a methodological aid, recommendations in the process of work of specialists in this field. The article describes the modern role and features of the organization of music circles in higher educational institutions, secondary schools and out-of-school educational institutions.